The Impact of Modern Macroeconomic Policies on Economic Growth, an Applied Study in Each of (Iraq, UAE, Egypt) During the Period (2000-2021) - kareem, Gazang khalid (Zanco Journal of Human Sciences, 2024)
The study aimed to identify modern macroeconomic policies (monetary and financial) and their role in achieving economic development in Iraq compared to the UAE and Egypt. Fiscal policy: (public spending and public revenues), and two aspects of monetary policy: (exchange rate, interest rate and volume of domestic credit granted to the private sector). For data for the period 2000-2021. The results of the study and the existence of a clear relationship and impact in the long run and at a high level between the independent variables of each of monetary and fiscal policy and the dependent variable in economic growth, and this means that both fiscal and monetary policies contribute to influencing economic growth. Government spending was more effective in influencing economic growth than the impact of monetary policy. The researcher made a number of important recommendations to achieve economic stability